Development of Delirium in the Intensive Care Unit in Patients after Endovascular Aortic Repair: A Retrospective Evaluation of the Prevalence and Risk Factors. (2nd September 2015) - Kawatani, Yohei; Nakamura, Yoshitsugu; Hayashi, Yujiro; Taneichi, Tetsuyoshi; Ito, Yujiro; Kurobe, Hirotsugu; Suda, Yuji; Hori, Takaki
Abstract : Delirium is an acute form of nervous system dysfunction often observed in patients in the intensive care unit. Endovascular aortic repair (EVAR) is considered a minimally invasive surgical treatment for abdominal aortic aneurysm. Although the operation method is widely used, there are few investigations of the rate and risk factors of delirium development after the operation. In this study, we retrospectively examined the rate of delirium development in the intensive care unit (ICU) after EVAR, as well as the associated preoperative risk factors and effects on the lengths of ICU and hospital stays. We examined the 81 consecutive patients who underwent elective EVAR between November 2013 and August 2014. The Intensive Care Delirium Screening Checklist was used to diagnose delirium. Twenty patients (24.7%) were diagnosed with delirium in this study. The ICU and hospital length of stays of patients with delirium were 3.3 ± 2.4 days and 14.5 ± 11.9 days, respectively, the latter of which was significantly longer than that of patients without delirium (p =   0.019 ). Additionally, renal dysfunction, preoperative benzodiazepine use, and intraoperative transfusion were found to be risk factors for the development of delirium after elective EVAR.